Information in Pursuit of the "Good Death": Libraries’ Role in the Death Positivity Movement - Chabot, Roger (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
The Death Positivity Movement (DPM) is a recent social and activist movement seeking to change the North American “culture of silence” surrounding death and dying. Seeking to engage with the conference theme of “conversations across boundaries,” this presentation presents arguments as to why libraries should be involved in the movement and also outlines more specifically actions that they can take to be involved. In this presentation, a short introduction to the DPM will be provided, followed by a brief discussion of the concept of the “good death”. Arguments will then be made explaining why libraries should be involved in the DPM and then the last section explores more specifically how libraries can be involved through collection development, community assistance and programming.